MEASURING THE EFFICIENCY OF LOCAL GOVERNMENT UNITS MANAGEMENT IN THE CENTRAL REGION OF POLAND IN A DYNAMIC PERSPECTIVE - Miszczyński, Piotr M. (Metody Ilościowe w Badaniach Ekonomicznych, 2013)
Local government units in Poland are obliged to improve the quality of life of their inhabitants concerning rules of sustainable development. The study described in the article is intended to measure the relative efficiency of management including examination of the relationship between various inputs and outputs in local government units. The analysis in the paper shows efficiency differences between local governments in comparison with sub-region leaders (group frontiers) and region leaders (meta-frontiers). The division into sub-regions and regions was made according to NUTS classification. The measurement of inputs and outputs in local government management units was based on indicators of sustainable development from SAS (Local Government Research System) database. Apart from static comparison (for a particular year) the main purpose of the article is to show changes of efficiency in 5 years horizon with application of dynamic meta-frontier approach. The outcome of the analysis made it possible to indicate some reference points (benchmarks), which may contribute to improve the efficiency of management in the local government units in Poland under research. The concepts delivered in the paper are employed for the purpose of assessing growth performance of local governments using a data set covering 128 cities in period 2006-2010